University of the future: A conceptual business model of University Putra Malaysia - Faizan, Faizullah; Ghafari, Abdullah; Hussein, Mohamed; Ahmad Dahlan, Abdul Rahman (Research Publish Journal, 2018)
Higher education enrolment in Malaysia has increased over the last 10 years. Malaysia must continuously improve to thrive in an increasingly competitive global economic environment including the transformation of its Higher education system. One of the transformation initiatives is the digital transformation of the Malaysian universities. Hence, the focus of this paper is to digitally transform University Putra Malaysia (UPM). The methodology used is based on COBIT implementation framework, literature review, interview, and business modelling framework. The main contribution of this paper is the conceptual business model and game changers specifically for UPM, and generally for other universities.